Assessment of mothers' knowledge and practices towards their children with cerebral palsy in a rehabilitation center (The International Journal for Scientific Research, 2025)
Background: The Cerebral Palsy Center works closely with rehabilitation, including occupational, physical and speech therapists under a good regulation.Aim: To evaluate knowledge and practice on mothers who have children suffering from cerebral palsy which attend to rehabilitation centers Methods: This rehabilitation centers-based cross-sectional study was conducted in order to assess the knowledge and practices of the70 Mothers attending to Cheshire home and Osratna rehabilitation center, Sudan center and Sakena center with their children diagnosis cerebral palsy during the study period. Cerebral palsy was defined as mothers knowledge and practice, beside mothers group discussion and interview for employees.Result: Result: 42.33% of mothers had no idea about the disease causing their children's disability, and 51.9% of them applied practical treatment procedures accurately to their children with disabilities.Conclusion: Most mothers have poor knowledge of the nature of cerebral palsy, which can lead to serious consequences. Overall, most mothers reported unsatisfactory work practices. There is a statistically significant relationship between mothers' sociodemographic data, their knowledge, and reported practices.Recommendations: Provide an education program for mothers about prenatal care and, how to care for children with cerebral palsy design booklets and leaflet.
Keywords: Mothers' Knowledge; Mothers' Practices; Children; Cerebral Palsy; Rehabilitation Center